Obstacles Obsessions and Prospects of Turkey's EU Membership - Akgün, İbrahim Mensur; Tiryaki, Sylvia (My University, 2011)
Turkey has aspired to become a member of the EU since 1959 and has managed to accomplish several significant milestones toward that goal. However, the accession talks are progressing rather slowly and Turkey still seems to be far away from full membership. The authors argue that obstacles delaying the process can be summarized into two primary categories: cultural differences, which are often reduced to the notion of religion, and impediments linked to the Cyprus problem. The paper will assert that without a settlement of the problem on the Mediterranean island, Turkey’s membership prospects are likely to remain uncertain. Following this line of reasoning, it will be claimed that a strategic vision of the EU can bring an end to the existing conundrum in the accession talks. Such an active move forward is in the interest of the EU, especially as Turkey becomes a more active player in the arena of international relations. Some indicators show a change in that direction, such as Lady Ashton’s comment in her capacity as High Representative: “We welcome the increasingly important role of Turkey in the region. In this context we will also look at the ways in which the EU and Turkey can enhance cooperation.” The issues that the EU tries to tackle are within the problemsolving vision of Turkey. Therefore it will be argued that if Turkey firmly establishes itself as a major regional player, it would likely play a crucial role in the success of the EU’s foreign policy, if admitted to the EU.